2023
DOI: 10.3390/s23052635
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Velocity Measurement for Enhancing Laser UltraSound Imaging Based on Time Domain Synthetic Aperture Focusing Technique

Abstract: A method to enhance laser ultrasound (LUS) image reconstruction with the time-domain synthetic aperture focusing technique (T-SAFT) is presented, in which the acoustic velocity is extracted in situ with curve fitting. The operational principle is provided with the help of a numerical simulation, and the confirmation is provided experimentally. In these experiments, an all-optic LUS system was developed by using lasers for both excitation and detection of ultrasound. The acoustic velocity of a specimen was extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Their study included a pulsed laser beam to generate waves that scanned over the test surface, which were produced by conventional ultrasonic transducers. Yoon T et al [28] analyzed the influence of acoustic velocity during the image reconstruction process by using the laser ultrasonic T-SAFT and concluded that accurate acoustic velocity extraction could enhance the visibility in reconstructed images. Ying KN et al [29] investigated the directivity patterns of multi-modes, which were generated via pulsed laser beam, and adapted these multi-modes to generate inspection images via the T-SAFT algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Their study included a pulsed laser beam to generate waves that scanned over the test surface, which were produced by conventional ultrasonic transducers. Yoon T et al [28] analyzed the influence of acoustic velocity during the image reconstruction process by using the laser ultrasonic T-SAFT and concluded that accurate acoustic velocity extraction could enhance the visibility in reconstructed images. Ying KN et al [29] investigated the directivity patterns of multi-modes, which were generated via pulsed laser beam, and adapted these multi-modes to generate inspection images via the T-SAFT algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Ying [ 26 ] proposed a Multi-mode Time-domain SAFT algorithm, which can be used to superimpose SAFT images generated by single-mode ultrasound signals to obtain a better defect shape. Yoon [ 27 ] presented a method to enhance laser ultrasound image reconstruction with the time-domain synthetic aperture focusing technique, in which the acoustic velocity is extracted in situ with curve fitting. As for cylindrical components, Li [ 28 ] established a theoretical model of the forward vector algorithm for an ultrasonic immersion curved surface to improve the detection speed.…”
Section: Introductionmentioning
confidence: 99%